The wealth building home loan - Edward J. Pinto; Stephen D. Oliner; Tobias Peter (American Enterprise Institute (AEI), 2018)
The Wealth Building Home Loan (WBHL) represents a class of shorter-maturity mortgages that provide a low-risk path to homeownership and wealth accumulation while maximizing buying power. WBHLs are easy-to-understand loans that combine standard mortgage features in a novel way. Importantly, they require little or no downpayment. The WBHLs in the market today are 15- and 20-year loans, some with fixed rates and others structured as adjustable-rate mortgages (ARMs). We show that a 20-year WBHL can be structured to have monthly payments for many borrowers that are only slightly higher than for the typical FHA 30-year fixed rate mortgage (FRM), due in part to the use of an ARM structure with a low initial rate. Shorter-maturity ARMs carry much less risk of payment shock, and hence are a safer choice, than 30-year ARMs. We also show that the use of 15- and 20-year loans would have greatly reduced the incidence of negative equity during the financial crisis and that the actual default rates on these loans during that period were much lower than for observably equivalent 30-year FRMs. These results highlight that widespread use of WHBLs would have substantial benefits for borrowers, lenders, and the financial system as a whole.
Keywords: A; 330; Financial system; mortgage; Housing finance; Housing Center: Initiatives; Housing Center: Research; Housing Center: Wealth-Building Home Loan